Effect of processing conditions on the dispersion of carbon nanotubes in polyacrylonitrile solutions. Issue 26 (31st March 2015) - Yan, Xuejia; Dong, Hongming; Liu, Yaodong; Newcomb, Bradley A.; Chae, Han Gi; Kumar, Satish; Xiao, Zhiwei; Liu, Tao
ABSTRACT As a result of van der Waal's interactions, carbon nanotubes (CNTs) tend to assemble into bundle/rope structures. It is essential to de‐bundle and exfoliate CNTs in polymer solutions in order to utilize their reinforcement potential as far as possible. In this study, a variety of different processing conditions were used to prepare polyacrylonitrile/CNTs composite solutions. The CNT bundle diameter, length, and macro‐scale dispersion homogeneity in those solutions were compared. It was observed that the CNT type, solvent type, and polymer concentration were important factors to determine the CNT bundle sizes in the solutions. The results are expected to be beneficial to obtain well‐dispersed polymer/CNT nanocomposites. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42177.